Self-medication in time of pandemic: Covid-19 - Navarrete-Mejía, Pedro Javier (2021)
Objetive. To know the characteristics of self-medication as a preventive or symptomatic treatment in the previous stage and against the COVID pandemic 19. Materials and methods: observational-descriptive study, 790 inhabitants of the districts of North Lima participated, both sexes, over 18 years, voluntary participation. A questionnaire was completed with sociodemographic variables, educational level, comorbidities, pre-pandemic self-medication, pandemic self-medication, health professional / technical condition, and drugs; analysis of descriptive data and student's t-tests, pearson's Chi square (significance level 95%). Results: mean age 40.87 years, 51.08% female, primary / secondary education in 61.0% of cases; comorbidities present, at the time of data collection, high blood pressure (15.4%), overweight / obesity (13.7%), diabetes (7.1%) and cancer (4.6%). The most widely consumed drugs, self-medicated, prior to the start of the pandemic, pain reliever (29.1%), anti-inflammatories (28.1%) and antibiotics (27.6%); during the pandemic, antibiotics / anti-inflammatories (39.2%), anti-inflammatory (30.9%), antibiotics (21.6%), ivermectin (5.7%) and ivermectin in combination with other drugs (2.6%). Increase in the number of women who self-medicate as a preventive measure or symptomatic treatment in a pandemic (p = 0.0001), a similar situation with people with overweight / obesity (p = 0.001) and cancer (p = 0.023). Conclusions: variables around self-medication changed, age decreased and the number of women increased. The frequency of drugs and type also changed, going from higher consumption of pain relievers and anti-inflammatory drugs to greater consumption of antibiotics / anti-inflammatory drugs and medications such as ivermectin (alone or in combination). Self-medication is a problem for health systems, even more so without the effect of drugs on the SRS Cov2 being known; The actions for compliance with the General Health Law No. 26842 should be strengthened, a stricter control of the aspects related to the sale of medicines is urgent.